One-step transformation with site-specific recombinase Cre/loxP system under the control of minimal 35S promoter for the development of marker-free transgenic Arabidopsis thaliana plants - Sekan, A. S.; Isaenkov, S.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
In a number of works, the successful use of the site-specific recombinase system Cre/loxP under the control of chemical promoters to obtain marker-free transgenic plants was described. However, providing the transformation process with the conditional or another kind of treatment to initiate the recombinase expression is the disadvantage of this method. We have developed a new approach in the site-specific recombinase system Cre/loxP to produce marker-free genetically modified plants without any treatment and shown the efficiency of Cre recombinase in the progeny of transformed plants A. thaliana.